2015
DOI: 10.1002/pssa.201532167
|View full text |Cite
|
Sign up to set email alerts
|

The influence of HTHP treatment on the OK1 and N3 centers in natural diamond crystals

Abstract: The structures of nitrogen-containing paramagnetic centers OK1 and N3 have not been unambiguously determined yet. In this paper, we will present data on the influence of high temperature annealing on the paramagnetic centers OK1 and N3 in diamond. A series of natural colored diamond crystals of cubic habit containing paramagnetic centers OK1 and N3 was studied by electron paramagnetic resonance (EPR), luminescence, and IR spectroscopies. It was found that annealing at temperatures above 2470 K led to the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…This centre has previously been detected in many yellow cuboid diamonds (Zudina et al 2013;Zedgenizov et al 2016). The correlation between the 635.7 nm luminescence system and the N3 centre detected by EPR has recently been demonstrated by Nadolinny et al (2015). However, although we observed the 635.7 nm system in yellow cuboid diamonds we did not detect the N3 centre with EPR.…”
Section: Nm Excited Plsupporting
confidence: 52%
See 1 more Smart Citation
“…This centre has previously been detected in many yellow cuboid diamonds (Zudina et al 2013;Zedgenizov et al 2016). The correlation between the 635.7 nm luminescence system and the N3 centre detected by EPR has recently been demonstrated by Nadolinny et al (2015). However, although we observed the 635.7 nm system in yellow cuboid diamonds we did not detect the N3 centre with EPR.…”
Section: Nm Excited Plsupporting
confidence: 52%
“…Recently it has been found that in natural diamonds from eclogitic xenoliths the detection of paramagnetic OK1 and N3 centres correlated with the abundance of titanium compounds (Nadolinny et al 2009b(Nadolinny et al , 2012(Nadolinny et al and 2015. The samples with observed OK1 and N3 centres have low total nitrogen concentration of about 10 ppm because the titanium is the nitrogen getter (Nadolinny et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the phonon structure of the N3/440.3 nm center showed that the energy of the quasi-local vibration (53 meV) corresponded to the titanium atom mass [33]. Annealing of natural diamond crystals at 2500 K for two hours showed that the N3 paramagnetic center transformed into OK1 paramagnetic centers [37]. Table 3.…”
Section: Titanium-containing Centers In Diamondmentioning
confidence: 99%
“…Общее содержание примесного азота в них колеблется в пределах от 56 до 1200 ppm. По данным ФЛ, в 18 из 25 кристаллов кубического габитуса наблюдается электронно-колебательная система (ЭКС) 635,7 нм [10], в 13 кристаллах присутствуют азотно-титановые центры с эмиссией S1 (OK1 в спектрах ЭПР), и в одном из этих кристаллов наблюдается ЭКС с бесфононной линией (БФЛ) 485 нм, ответственная за проявление парамагнитного азотно-титанового центра NU1 со структурой расщеплённой по <100> межузельной конфигурации [8]. По данным ЭПР в вышеперечисленных 18 кристаллах регистрируется азотно-титановый центр N3.…”
unclassified
“…Но в отличие от ранее изученных кристаллов алмаза октаэдрического габитуса [8], в кубах из россыпи Исток не регистрируется оптическая система с БФЛ 440,3 нм, ранее отнесённая к проявлению азотно-титанового центра N3. В работе [10] отмечалось, что в кристаллах кубического и кубо-октаэдрического габитуса из других месторождений регистрируются в спектрах ЭПР центры ОК1 и N3, а в люминесценции оптические системы S1 и 635,7 нм. Слабая оптическая система с БФЛ 440,3 нм отмечалась только в пяти кристаллах.…”
unclassified